2012
DOI: 10.1111/j.1440-1746.2011.06928.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the putative intestinal stem cell marker doublecortin and CaM kinase‐like‐1 in Barrett's esophagus and esophageal adenocarcinoma

Abstract: Background In Barrett’s esophagus (BE), the normal esophageal squamous epithelium is replaced by specialized metaplastic columnar epithelium. BE is a premalignant lesion which can progress to esophageal adenocarcinoma (EAC). Currently there are no early molecular indicators that would predict progression from BE to EAC. As the only permanent residents of the epithelium, stem cells have been implicated in this metaplastic progression. Aim To determine the expression of DCAMKL-1 and other putative gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Upon isolation, intestinal DCLK1 + cells formed primitive epithelial spheres (24). Moreover, DCLK1 + tuft cells are substantially increased in a number of models of inflammation-induced carcinogenesis, arguing for a possible role in malignant transformation (26)(27)(28). Recently, Nakanishi and colleagues described the generation of a Dclk1-CreERT 2 knockin mouse that allowed formal lineage tracing.…”
Section: Introductionmentioning
confidence: 99%
“…Upon isolation, intestinal DCLK1 + cells formed primitive epithelial spheres (24). Moreover, DCLK1 + tuft cells are substantially increased in a number of models of inflammation-induced carcinogenesis, arguing for a possible role in malignant transformation (26)(27)(28). Recently, Nakanishi and colleagues described the generation of a Dclk1-CreERT 2 knockin mouse that allowed formal lineage tracing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that DCLK1 may mark cancer stem cells in gastrointestinal and other cancers (10,24), while others have identified DCLK1 upregulation in several types of cancer, including esophageal, stomach, colorectal, pancreatic and liver cancer (8,(13)(14)(15)(16)(17)(18). In addition, increased DCLK1 expression has been identified in Barrett's esophagus, a premalignant lesion that can progress to esophageal adenocarcinoma, and may be regarded as an early molecular predictor of tumor progression (18). Although DCLK1 has been demonstrated to be upregulated in human colorectal adenoma and cancer (13), studies on the expression of DCLK1 in serrated tumor tissue are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise tumor-promoting mechanism of DCLK1 is yet to be determined, it has been demonstrated that reduced DCLK1 expression correlates with increased expression of tumor suppressor microRNAs (miRs), including miR-145, miR-200 and let-7a (11,12). Indeed, DCLK1 has been indicated to function as an oncogene in several types of tumor, including CRC (13)(14)(15), pancreatic cancer (8), hepatocellular carcinoma (16), gastric cancer (17) and Barrett's adenocarcinoma (18).…”
Section: Introductionmentioning
confidence: 99%
“…72 In our L2-IL-1b mouse model and in human BE, we found an accumulation of Dclk1+ cells, and this was confirmed in a study by another group, which reported a progressive increase of Dclk1 expression in BE from dysplasia to EAC. 73 Dclk1+ cells are highly abundant in the gastric cardia, particularly in areas immediately adjacent to the SCJ. segment can be clonally derived, with rapid spread of mutations through the epithelium.…”
Section: Cell Of Origin Of Barrett Esophagusmentioning
confidence: 99%